1998
DOI: 10.1021/jp981208y
|View full text |Cite
|
Sign up to set email alerts
|

Charge Separation in Photosynthetic Reaction Centers

Abstract: Structural influences on the direction of electron transfer in the charge separation process of the photosynthetic reaction centers of Rhodopseudomonas viridis and Rhodobacter sphaeroides are studied using quantum chemical models to calculate the electronic factor. Our results support the sequential mechanism for the primary charge separation. Using crystallographic coordinates refined in 1994, we find a larger coupling between the special pair D and the accessory bacteriochlorophyll BA of the A branch than be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 47 publications
(84 reference statements)
1
58
0
Order By: Relevance
“…8,[13][14][15] Here we have re-examined V for P/B A and P/B B using the coordinates of Rb. sphaeroides, at a resolution of 2.2 Å, 16 and of Rps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,[13][14][15] Here we have re-examined V for P/B A and P/B B using the coordinates of Rb. sphaeroides, at a resolution of 2.2 Å, 16 and of Rps.…”
Section: Introductionmentioning
confidence: 99%
“…The opinions vary from total neglect of the hyperconjugated group 22 to assigning to them the main contribution. 14 Also it is not clear whether hyperconjugated groups facilitate the MCs by extending the MOs 14 or the "hole transfer" through occupied hyperconjugated groups contributes negative components to the MC. 27 We assume that when the through-space atomic couplings are properly considered, the extension of the MOs is not necessary for having a reasonable estimate of the coupling.…”
Section: Introductionmentioning
confidence: 99%
“…59,60,61,62 The symmetry is already broken at the special pair with selective chargetransfer reactivity towards the L side and it has been suggested that the L side molecule has a less distorted macrocycle than the M side chromophore. 63,64 While other explanations have been brought forward, 65 there is structural evidence for multiple conformations in protein structures from site-directed mutants. 66 Resonance Raman and other vibrational techniques have been used to investigate this situation and have provided supporting information for structural flexibility of the chromophores.…”
Section: Chlorophyll Complexes In Photosynthesismentioning
confidence: 99%
“…From (19) follows the relation for determining the electronic transition matrix element (20); γ 0 , k 0 from Tables 1, 2 10.5 [74] INDO/S; for P * → B L 24 [16] From formula (2)…”
mentioning
confidence: 99%